The potential link between inherited G6PD deficiency, oxidative stress, and vitamin D deficiency and the racial inequities in mortality associated with COVID-19 - Jain, Sushil K.; Parsanathan, Rajesh; Levine, Steve N.; Bocchini, Joseph A.; Holick, Michael F.; Vanchiere, John A. (Free radical biology & medicine, 2020)
There is a marked variation in mortality risk associated with COVID-19 infection in the general population. Low socioeconomic status and other social determinants have been discussed as possible causes for the higher burden in African American communities compared with white communities. Beyond the social determinants, the biochemical mechanism that predisposes individual subjects or communities to the development of excess and serious complications associated with COVID-19 infection is not clear. Virus infection triggers massive ROS production and oxidative damage. Glutathione (GSH) is essential and protects the body from the harmful effects of oxidative damage from excess reactive oxygen radicals. GSH is also required to maintain the VD-metabolism genes and circulating levels of 25-hydroxyvitamin D (25(OH)VD). Glucose-6-phosphate dehydrogenase (G6PD) is necessary to prevent the exhaustion and depletion of cellular GSH. X-linked genetic G6PD deficiency is common in the AA population and predominantly in males. Acquired deficiency of G6PD has been widely reported in subjects with conditions of obesity and diabetes. This suggests that individuals with G6PD deficiency are vulnerable to excess oxidative stress and at a higher risk for inadequacy or deficiency of 25(OH)VD, leaving the body unable to protect its ‘oxidative immune-metabolic’ physiological functions from the insults of COVID-19. An association between subclinical interstitial lung disease with 25(OH)VD deficiencies and GSH deficiencies has been previously reported. We hypothesize that the overproduction of ROS and excess oxidative damage is responsible for the impaired immunity, secretion of the cytokine storm, and onset of pulmonary dysfunction in response to the COVID-19 infection. The co-optimization of impaired glutathione redox status and excess 25(OH)VD deficiencies has the potential to reduce oxidative stress, boost immunity, and reduce the adverse clinical effects of COVID-19 infection in the AA population. [Display omitted] •African Americans (AA) have a higher incidence of serious complications associated with COVID-19.•Glucose-6-phosphate dehydrogenase and vitamin D (VD) deficiencies are common in AA.•Excess oxidative damage can cause a cytokine storm and impair immunity.•Optimization of VD and glutathione has potential to reduce oxidative stress and adverse clinical effects of COVID-19.